CLIMATE CHANGE AND THE LEGAL TREATMENT OF ENVIRONMENTAL REFUGEES - Torres, Nicholas Salles Fernandes Silva; Campello, Lívia Gaigher Bósio (Revista de Direito Brasileira, 2017)
The intensification of extreme weather events caused by climate changes has contributed to the massive displacement of people in the most vulnerable regions, causing an unprecedented migratory flow. Given this situation, and given the low capacity of resilience of the population and of the States that suffer such natural consequences, particularly in developing countries and small island countries, there is a growing concern about the lack of legal protection to such individuals. Therefore, because of the lack of adequate international protection for environmental refugees and an alarming regulatory gap, it is necessary to adopt urgent measures for the protection, mitigation and adaptation to minimize the impacts caused by climate change and protect the most vulnerable populations, forced to leave their States in search of better living conditions. In the present bibliographical and documentary research, the deductive method was used.